2012
DOI: 10.1074/jbc.m112.399964
|View full text |Cite
|
Sign up to set email alerts
|

RNase L Induces Autophagy via c-Jun N-terminal Kinase and Double-stranded RNA-dependent Protein Kinase Signaling Pathways

Abstract: Background: Autophagy is induced by stress, starvation, and viral infections; however, the role of RNase L in autophagy has not been investigated. Results: Activation of RNase L induces autophagy involving JNK and PKR. Conclusion: Autophagy induced by activation of RNase L modulates viral growth. Significance: Our findings identify a novel role of RNase L in inducing autophagy affecting outcomes of viral infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
70
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 66 publications
4
70
0
Order By: Relevance
“…The context of the infected cell provides multiple potential sources of signals for autophagy induction. For example, protein kinase R (PKR) and RNase L, which are activated by dsRNA, a pathogen-associated molecular pattern characteristic of viruses such as EHDV, were implicated in the induction of autophagy (23,49,50). Indeed, the infection-dependent phosphorylation of the translation regulator eIF2␣ (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The context of the infected cell provides multiple potential sources of signals for autophagy induction. For example, protein kinase R (PKR) and RNase L, which are activated by dsRNA, a pathogen-associated molecular pattern characteristic of viruses such as EHDV, were implicated in the induction of autophagy (23,49,50). Indeed, the infection-dependent phosphorylation of the translation regulator eIF2␣ (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that small differences in cell culture conditions and starvation conditions may contribute to discrepancies between our analysis (Figure 2) and previously published reports of the role of MAPK8/9 in MEFs [5]. The use of the small molecule SP600125, that inhibits MAPK8/9 and many other protein kinases [52], to draw conclusions concerning the specific role of MAPK8/9 may also contribute to conclusions [8,10,1219,22,51] that contrast with those drawn from our analysis of MAPK8/9 knockout cells. Finally, some studies that have identified a role for MAPK8/9 do not focus on starvation-induced autophagy.…”
Section: Discussionmentioning
confidence: 67%
“…Knock-down of endogenous proteins was determined by western blotting. Transfection of 2–5A (10 μM) was performed using lipofectamine 2000 (Invitrogen, Thermo Fisher Scientific, Waltham, MA, USA) according to the manufacturer’s protocol as described previously [75]. Briefly, cells were plated 1 day before transfection, so that the cells are 80%–90% confluent at the time of transfection.…”
Section: Methodsmentioning
confidence: 99%
“…2–5A was diluted into serum-free media and then mixed with lipofectamine 2000 reagent for 15 min before being added to cells in growth media. Preparation of 2–5A using ATP and recombinant 2–5A synthetase (a generous gift from Rune Hartmann, University of Aarhus, Aarhus, Denmark) has been described previously [75]. PolyI:C (2 μg/mL) was transfected into cells using Polyjet reagent (SignaGen Laboratories, Gaithersburg, MD, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation